ANALISIS PENGARUH PELATIHAN, INSENTIF DAN LINGKUNGAN KERJA TERHADAP KINERJA ATC (AIR TRAFFIC CONTROLLER) PADA PERUM LPPNPI CABANG YOGYAKARTA - Nyoman Dicky Surya Negara; S. Subarjo (Warmadewa Management and Business Journal (WMBJ), 2022)
Understanding the importance of the existence of human resources in the current global era, one of the efforts that must be achieved by companies is to improve the quality of human resource performance. Therefore, this study aims to determine the factors that can affect the performance of employees at Perum LPPNPI Yogyakarta Branch. These factors are incentives, training and work environment. High performance will have a positive impact on the company / organization so that company goals can be achieved. Hypothesis testing was done by distributing questionnaires to employees of Perum LPPNPI Yogyakarta, especially ATC.Based on the results of the data calculation and analysis used, the regression equation is obtained, namely: Y = 10,162 (Î±) + 0,537 X1+ 0,246 X2 + 0,593 X3 Based on the analysis of the Multiple Regression Test conducted, it shows that the education variable has a t count value of 4.905 > t table 2.021 and a significance value of 0.000 < alpha 0.05. These results mean that Ho is rejected and Ha is accepted, which means that the training variable has a significant effect on employee performance. Based on the analysis of the Multiple Regression Test conducted, it shows that the incentive variable has a t count value of 3.350 > t table 2.021 and a significance value of 0.002 < alpha 0.05. These results mean that Ho is rejected and Ha is accepted, which means that the incentive variable has a significant effect on employee performance. Based on the analysis of the Multiple Regression Test conducted, it shows that the work environment variable has a t count value of 2.463 > t table 2.021 and a significance value of 0.018 < alpha 0.05. These results mean that Ho is rejected and Ha is accepted, which means that the work environment variable has a significant effect on employee performance.